Mitochondrial dysfunction and cell senescence: deciphering a complex relationship. Issue 13 (27th June 2019) - Chapman, James; Fielder, Edward; Passos, João F.
Abstract : Cellular senescence and mitochondrial dysfunction have both been defined as classical hallmarks of the ageing process. Here, we review the intricate relationship between the two. In the context of ageing, it is now well regarded that cellular senescence is a key driver in both ageing and the onset of a number of age‐related pathologies. Emerging evidence has pinpointed mitochondria as one of the key modulators in the development of the senescence phenotype, particularly the pro‐inflammatory senescence associated secretory phenotype (SASP). This review focuses on the contribution of homeostatic mechanisms, as well as of reactive oxygen species and mitochondrial metabolites in the senescence programme. Furthermore, we discuss emerging pathways and mitochondrial‐mediated mechanisms that may be influencing the SASP and, subsequently, explore how these may be exploited to open up new therapeutic avenues. Abstract :